Carbon stable isotope composition of DNA isolated from an incipient paleosol - Jahren, A. H.; Kelm, K.; Wendland, B.; Petersen, G.; Seberg, O. (Geology, 2006)
We determined the carbon isotope (delta(13)C) value of double-stranded DNA (dsDNA) isolated from the organic horizons of a Delaware soil that is actively being covered by an encroaching sand dune. The soil belongs to a Nymphaea odorata Ait. (water lily) wetland, and we regard its active acquisition of a thick (similar to 24 cm) surface mantle to embody the process of palleopedogenesis; therefore, we have termed it an "incipient paleosol." In this study, we compared the delta(13)C value of paleosoll dsDNA to the bulk delta(13)C value of N. odorata, as well as to the delta(13)C value of plants that had colonized the surface mantle. The isotopic offset between palleosol delta(13)C(dsDNA) and N. odorata delta(13)Ca(tissue) was identical to the relationship between delta(13)C(dsDNA) and delta(13)C(tissue) for tracheophytes, which we had previously determined. In contrast, the isotopic offset between paleosol delta(13)C(dsDNA) and the delta(13)C(tissue) of plants colonizing the surface mantle differed from this relationship by as much as 41%. Similarly, the delta(13)C value of bulk palleosoll organic matter was extremely heterogeneous and varied across 6%. All palleosol DNA pollymerase chain reaction (PCR) products produced clear, sharp, 350 base-pair (bp) fragments of rbcL, a gene shared by all photosynthetic organisms. These results open the exciting possibility that stable isotope analysis of dsDNA isolated from palleosol organic matter can be used to infer the delta(13)C value of the plant that dominated the nucleic acid contribution.
039nnTimes Cited:4Cited References Count:19